Dish-Stirling solar power plants: Modeling, Analysis, and Control of receiver temperature - Li, Y.; Choi, San Shing; Yang, C. (The Institute of Electrical and Electronic Engineers (IEEE), 2014)
A simplified adiabatic model of the Stirling engine is developed for the study of a grid-connected dish-Stirling solar-thermal power plant. The model relates the average values of the engine state variables and also takes into account the engine losses. As the engine is shown to exhibit nonminimum phase behavior, an improved temperature control scheme for the engine heat absorber is developed. By including the engine speed, pressure, and solar insolation limits into the analysis, a steady-state feasible operating regime of the solar-thermal power plant is obtained. A maximum solar energy harness is shown to be achievable through the variable speed operation of the power plant. © 2010-2012 IEEE.